Growth effects of wealth inequality through transmission channels - Seyed Armin Motahar; Siab Mamipour (Economies, 2025)
In light of the substantial rise in economic inequality in recent decades across the majority of economies, the relationship between inequality and economic growth has garnered significant attention. However, the specific impact of wealth inequality through various transmission channels on growth remains underexplored. This study underscores the limitations of relying on income inequality as a proxy for wealth disparities in growth research and emphasizes the importance of addressing nonlinearities in examining the relationship between inequality and growth. It pioneers the examination of transmission channels from wealth inequality to economic growth, employing an innovative nonlinear mediation analysis that incorporates both linear and nonlinear aspects, with the Generalized Additive Method utilized for the nonlinear part. Using the wealth Gini index as the primary measure of wealth inequality across a panel of 150 countries from 1980 to 2020, the findings indicate that inequality impedes growth via the human capital, socio-political stability, consumption, and innovation channels, while it exerts a positive influence through investment. The mediation effect of the rent-seeking channel is found to be nonsignificant. Above all, the study highlights the substantial negative impact of wealth inequality on innovation, a key driver of economic growth, underscoring the importance of addressing wealth disparities in future growth analyses and policy decisions.
Keywords: 330; wealth inequality; economic growth; transmission channels; nonlinearity